Effects of Microcystis aeruginosa Blooming on Community Wastewater Quality in Pond Technology System - ศรีชมภู, มัลลิกา; บุญประคอง, ทัศนีย์; จันทร์แก้ว, เกษม; ปัทมพิฑูร, ธนิศร์; เสมวิมล, นพวรรณ (KKU Science Journal, 2015)
Blooming of Cyanobacterium, Microcystis aeruginosa affected on wastewater quality inpond technology system of King’s initially Laem PhakBia Environmental Study and Development Project. Two months (January – February 2014) of water sampling in the oxidation pond were used for analyzing physical property, chemical property and amount of Cyanobacterium, M.aeruginosa. The results showed that averaged population densityof M.aeruginosa was increased from 1.88×106 to 1.31×108 cell/m3 in January, winter time with averaged water temperature 27.9°C. M.aeruginosa was decreased to 2.72×106 cell/m3 in February, beginning of summer time.Furthermore, blooming of M.aeruginosa affected on increasing of suspended solid (SS), total dissolved solid (TDS) and biological oxygen demand (BOD) which were higher than the water quality standard.